2004
DOI: 10.1016/j.vibspec.2003.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-induced conformational interconversion in carboxylic acids isolated in low-temperature rare-gas matrices

Abstract: An overview of our recent studies dealing with infrared-induced conformational interconversion of carboxylic acids isolated in rare-gas matrices is presented. Extensive rotational photoisomerization studies have been performed on formic acid, which is the simplest organic acid enabling this kind of processes. Formic acid has two conformers and interconversion between them can be induced by vibrational excitation. As such, it is an ideal model system to study the conformational dynamics of the carboxylic group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 43 publications
0
21
0
2
Order By: Relevance
“…The energy above which the quantum yield reaches a relatively stable value ͑4500 cm Ϫ1 ͒ agrees with the computational barrier height, which supports the theoretical estimation. The lack of evident mode specific effects on the quantum yield was also reported for formic acid in solid Ar 7,19,31 For both molecules, the range of excitation energies probed corresponds to the discrete region of vibrational states and, thus, mode specific effects are generally possible. We can speculate that the observed lack of mode specificity in the isomerization quantum yield is connected with a slow isomerization rate, allowing effective randomization of the excitation energy between various modes.…”
Section: A Quantum Yield For the Ir-induced Isomerizationsmentioning
confidence: 53%
See 1 more Smart Citation
“…The energy above which the quantum yield reaches a relatively stable value ͑4500 cm Ϫ1 ͒ agrees with the computational barrier height, which supports the theoretical estimation. The lack of evident mode specific effects on the quantum yield was also reported for formic acid in solid Ar 7,19,31 For both molecules, the range of excitation energies probed corresponds to the discrete region of vibrational states and, thus, mode specific effects are generally possible. We can speculate that the observed lack of mode specificity in the isomerization quantum yield is connected with a slow isomerization rate, allowing effective randomization of the excitation energy between various modes.…”
Section: A Quantum Yield For the Ir-induced Isomerizationsmentioning
confidence: 53%
“…3͒. 7,19,31 At energies below ϳ4400 cm Ϫ1 , the quantum yield depends strongly on the excitation energy.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] This process occurs when the energy deposited into the initially excited vibrational mode is transferred to the reaction coordinate. The mechanism of energy relaxation in the solid was described as a phonon-assisted intramolecular vibrational energy relaxation (IVR) where the lattice modes provide a thermal bath compensating the energy mismatch between the intramolecular vibrational states.…”
Section: Introductionmentioning
confidence: 99%
“…2 after correction of zero-point vibrational energy, showing that TT is the most stable conformer. This result is in contrast to the fact that general carboxylic acids prefer cis to trans conformation about the OCAOH bond in the COOH group [13][14][15][16][17][18][19], as described in Introduction, implying that TT of 2-PA is strongly stabilized by the IMHB of COOHÁ Á ÁN in spite of the repulsion between lone pairs of the two O atoms in the COOH group. This is supported by comparison of the OAH bond lengths; the r(OAH) of TT is longer than that of other conformers by $0.01 Å as shown in Table 1.…”
Section: Optimized Geometrical Structures Of 2-pa By Dft Calculationsmentioning
confidence: 60%
“…For example, the less stable conformers, trans, in formic acid [13][14][15], acetic acid [13,16,17], propionic acid [13,18], and benzoic acid [19] are produced from the more stable conformers, cis, by IR radiation and return to cis in darkness through hydrogen-atom tunneling. Another example is reported that the trans conformer of 2-chlorobenzoic acid produced from the cis conformer by UV irradiation is unable to exist stably even in a low-temperature argon matrix in spite of the stabilization due to the IMHB of COOHÁ Á ÁCl [20].…”
mentioning
confidence: 99%